Pollen Morphology of Stachys L. Spp. Growing in Iraq - A.Al-Bayati, M.KH (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present work included new information about pollen of eighteen Spp. of Stachys L. in Iraq ;showed their importance in diagnostsis. Pollen shapes in equatorial view were ellipsoid in most spp .and spherical - subspherical , spherical - subprolate and subprolate - ellipsoid in others; while they were spherical - subspherical in polar view . Pollen was tricolpate except St.iberica M.B.georgica Rech.f. & Ten. Which has tetracolpate and that was new for the genus. The smallest pollen were seen in St.kotschyi Boiss. & Hohen. but the biggest were in St.benthamiana Boiss.